Acute memory deficits in chemotherapy-treated adults. Issue 10 (26th November 2017) - Lindner, Oana C.; Mayes, Andrew; McCabe, Martin G.; Talmi, Deborah
ABSTRACT: Data from research on amnesia and epilepsy are equivocal with regards to the dissociation, shown in animal models, between rapid and slow long-term memory consolidation. Cancer treatments have lasting disruptive effects on memory and on brain structures associated with memory, but their acute effects on synaptic consolidation are unknown. We investigated the hypothesis that cancer treatment selectively impairs slow synaptic consolidation. Cancer patients and their matched controls were administered a novel list-learning task modelled on the Rey Auditory Verbal Learning Test. Learning, forgetting, and retrieval were tested before, and one day after patients' first chemotherapy treatment. Due to difficulties recruiting cancer patients at that sensitive time, we were only able to study 10 patients and their matched controls. Patients exhibited treatment-dependent accelerated forgetting over 24 hours compared to their own pre-treatment performance and to the performance of control participants, in agreement with our hypothesis. The number of intrusions increased after treatment, suggesting retrieval deficits. Future research with larger samples should adapt our methods to distinguish between consolidation and retrieval causes for treatment-dependent accelerated forgetting. The presence of significant accelerated forgetting in our small sample is indicative of a potentially large acute effect of chemotherapy treatment on forgetting, with potentially clinically relevant implications.